Penanaman Nilai-Nilai Multikultural yang Dipengaruhi oleh Kompetensi Komunikasi Guru di Sekolah Dasar Inklusi Trirenggo, Yogyakarta - Dwi Kartikawati; Djudjur Luciana Rajagukguk; Yayu Sriwartini (Universitas Andalas, 2019)
This research focused on the urgency of teachers’ communication competence in inculcating multicultural values at elementary schools, in this case, the inclusive elementary school of Trirenggo, Yogyakarta. Communication skills are an essential competency for teachers as stated in the Regulation of the Minister of Education No. 16 of 2007 dated May 4th, 2007. Teachers, as communicators, are the main factor in establishing effective communication in the learning process. In this case, a teacher with excellent communication skills would substantially determine a school’s success in the implementation of multicultural values. In order to analyze the subject, this study used a qualitative method, and the data were collected from three respondents from the inclusive elementary school of Trirenggo, Yogyakarta. The results indicated that teachers’ communication competency which consisted of three aspects, i.e. motivation, knowledge, and skills, was urgently required in order to achieve teaching goals. A competent teacher would significantly be able to establish a positive atmosphere and influence among students, thus, enable them to effectively inculcate the designated values. At this school, the multicultural values were integrated into teaching subjects, students’ assessment, specified learning methods, character development, and regular group activities.